The Usage of Online Classrooms during the COVID-19 in Bangladesh: Some Issues and Influences - Md. Abu Sadath; Jyothy Mondal; Abdullah-Al- Faisal; Sanjana Afrin Disha; Sarmin Fatema (Journal of Asian Social Science Research, 2022)
The purpose of this study is to find out how teachers and students felt about online classes in Bangladesh. During the COVID-19 pandemic, the education system in Bangladesh has made a change by delivering classes via online means. Therefore, this study examines teachers' and students' perspectives and concerns about taking online classes, which have become mandatory because of the COVID-19 pandemic. The data were collected by using an online survey method. The sample included 907 teachers and 1451 students from schools, colleges, and universities across Bangladesh's eight divisions. The data show that in the pandemic situation, a total of 80% of students were able to be connected with online education. Among them, 56% of students got no facilities regarding online classes from their educational institutions. To continue their study, 56% of the students wanted offline education. Likewise, it was tracked down that quality and convenient cooperation among students and instructors, specialized help accessibility, organized online class modules, and changes permitting the lead of reasonable exercises are largely fundamental elements in educators' and students’ fulfilment with online classes. The absence of typical classroom socializing, lack of face-to-face engagement with the teacher, and response time were among the major difficulties raised by the students. This study contributes significantly to the studies of the impact of COVID-19 on education particularly within developing countries. It also will have a significant impact on the government of Bangladesh's decision on how to continue online classes in the face of the epidemic and reopen Bangladesh's educational facilities.